Information Content in Stochastic Pulse Sequences of Intracellular Messengers - Givré, Alan; Ponce Dawson, Silvina (Frontiers in Physics, 2018)
Many cell signaling pathways rely on oscillatory messenger concentrations even to transduce aperiodic environmental changes. The universal second messenger calcium, Ca2+, often exhibits pulsatile behavior in the presence of constant concentrations of external ligands such as hormones or neurotransmitters. Even when the mean interpulse time is a function of the external ligand concentration, the pulse sequence is not regular. The analysis of intracellular Ca2+ pulses that involve Ca2+ release through inositol 1,4,5-trisphosphate (IP3) receptors led to a model with stochastic pulse firing with rate, lambda, and deterministic inhibition and recovery with rate, rho. In this paper we combine this model with recent observations that established an exponential relationship between lambda and the external ligand concentration, C. We compute analytically the mutual information between C and the interpulse time or the number of pulses using the least informative distribution for C in the limits of lambda/rho<<1 and lambda/ρ>>1. We obtain that the mutual information is largest in the second limit. The difference between the two, however, is at most 1 bit. Thus, the resolution with which the values of C can be discriminated at most doubles in one case with respect to the other. The generic features of the model and the exponential dependence of the firing rate with C are an indication that the Ca2+ signaling mechanism behaves as a noise-driven excitable system. Our results are thus applicable in this more general setting as well.